PENGEMBANGAN E-MODUL BIOTEKNOLOGI BERBASIS ETNOSAINS DALAM PEMBELAJARAN ILMU PENGETAHUAN ALAM - Hielaria Aprila; Eny Enawaty; Fadillah Fadillah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractE-Module is an electronic teaching material that is included in the interactive teachingmaterial category because it combines text, images, and video, and requires usercontrol to take advantage of this teaching material. This research is aimed to develop e-module biotecnology etnoscience in science instructional. E-module was developedusing the Dick & Carey model which includes ten stages. This research was conductedat SMP N 2 Jagoi Babang by involving material experts, design experts, media experts,teachers and students. Data obtained were analyzed with quantitative and qualitativeanalysis. In quantitative analysis descriptive statistical analysis, the mean showed inpercentage, T-test for paired samples and the effectiveness test with N-Gain score. Theresults of the analysis showed positive responses from students (very good) and from thedifferent tests between before and after using e-module biotechnology etnoscience withthe T-test showed there were significant differences, it can be concluded through theeffectiveness test conducted with N-gain score with enough effective categories used inscience instructional.Keywords: Biotechnology, E-Module, Etnoscience